Determinan Kinerja Keuangan Perusahaan - Mujiyati, M; Susilowati, Kartiningsih (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
This research aims to determine the influence of the board ofdirectors, board of commissioners, audit committee, and companysize to the company's financial performance. The sample used in thisresearch were 53 manufactur companies sub-sector food andbeverage listed on Indonesia Stock Exchange (BEI) period 2014 to2018. The sampling method uses purposive sampling method. Theanalysis in this research uses the method of multiple linear analysis.The results of this research can be seen that the board of directors,board of commissioners, and company size have influence to thecompany's financial performance. While the audit committee have noinfluence to the company's financial performance.